Effect of 3D Manipulatives on Students with Visual Impairments Who Are Learning Chemistry Constructs: A Pilot Study. (September 2020) - Smith, Derrick W.; Lampley, Sandra A.; Dolan, Bob; Williams, Greg; Schleppenbach, David; Blair, Morgan
Introduction: The emerging technology of three-dimensional (3D) printing has the potential to provide unique 3D modeling to support specific content in science, technology, engineering, and mathematics (STEM) education, particularly chemistry. Method: Seventeen ( n = 17) students with visual impairments were provided direct instruction on chemistry atomic orbital content and allowed to use either print or tactile graphics or 3D models in rotating order. Participants were asked specific content questions based upon the atomic orbitals. Results: The students were asked two sets of comprehension questions: general and specific. Overall, students' responses for general questions increased per iteration regardless of which manipulative was used. For specific questions, the students answered more questions correctly when using the 3D model regardless of order. When asked about their perceptions toward the manipulatives, the students preferred the 3D model over print or tactile graphics. Discussion: The findings show the potential for 3D printed materials in learning complex STEM content. Although the students preferred the 3D models, they all mentioned that a combination of manipulatives helped them better understand the material. Implications for practitioners: Practitioners should consider the use of manipulatives that include 3D printed materials to support STEM education.